Custom in International Economic Law - Menkes, Jerzy (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The ‘old’ source of the international law – in the sense of the form of law-making – constituted by ‘custom’ does not lose its position in the catalogue of international law sources. On the contrary, its significance increases in the realm of international economic law. Moreover, ‘custom’ is also a vehicle for introducing ‘the new-generation law’, which is responsive and created by self-regulation, into international economic law.
Keywords: międzynarodowe prawo gospodarcze; prawo zwyczajowe; źródła; samoregulacja